Selecting Resort Locations. (December 2013) - Juan, Pin-Ju; Lin, Shin-Yi
This study examines a comprehensive and objective three-stage method for selecting resort location in Taiwan that maximize competitive advantage. The factors and criteria used in the evaluation model are obtained from an exhaustive literature review and interviews with 16 experts. In the first stage, for which the modified Delphi method is used to identify the evaluation criteria, a survey is performed to rank the relative importance of the 22 criteria identified in the interviews. In the second stage, 19 experts evaluate potential resort locations using a subjective multi-criteria model, the analytical hierarchy process (AHP). The analytical results yield rankings of resorts of the following types: casino resorts, seaside resorts, health/spa resorts and lakeside resorts. In the final stage, a sensitivity analysis is performed to clarify the strength of the various influences on resort selection. The analytical results are used to develop and examine a potential solution.